Connexin hemichannels and cell-cell channels: comparison of properties - Verselis,V.K. (2000)
Connexin46 (Cx46) forms functional hemichannels in the absence of contact by an apposed hemichannel and we have used these hemichannels to study gating and permeation at the single channel level with high time resolution. Using both cell-attached and -excised patch configurations, we find that single Cx46 hemichannels exhibit some properties expected of half of a gap junction channel, as well as novel properties. Cx46 hemichannels have a large unitary conductance (~300 pS) and a relatively large pore as inferred from permeability to TEA. Both monovalent cations and anions can permeate, but cations are substantially more permeable. The open channel conductance shows marked inward rectification in symmetric salts. We find that the conductance and permeability properties of Cx46 cell-cell channels can be explained by the series addition of two hemichannels. These data suggest that the pore structures of unapposed hemichannels and cell-cell channels are conserved. Also like cell-cell channels, unapposed Cx46 hemichannels are closed by elevated levels of H+ or Ca2+ ions on the cytoplasmic face. Closure occurs in excised patches indicating that the actions of these agents do not require a soluble cytoplasmic factor. Fast (<0.5 ms) application of H+ to either side of the open hemichannel causes an immediate small reduction in unitary conductance followed by complete closure with latencies that are dependent on H+ concentration and side of application; sensitivity is much greater to H+ on the cytoplasmic side. Closure by cytoplasmic H+ does not require that the hemichannel be open. Thus, H+ ions readily permeate Cx46 hemichannels, but at high enough concentration close them by acting at a cytoplasmic site(s) that causes a conformational change resulting in complete closure. Extracellular H+ may permeate to act on the cytoplasmic site or act on a lower affinity extracellular site. Thus, the unapposed hemichannel is a valuable tool in addressing fundamental questions concerning the operation of gap junction channels that are difficult to answer by existing methods. The ability of Cx46, and perhaps other connexins, to form functional unapposed hemichannels that are opened by moderate depolarization may represent an unexplored role of connexins as mediators of transport across the plasma membrane.